ASCORBIC ACID AND PHENOLIC SUBSTANCES IN THE UNFORTIFIED WILD STRAWBERRY WINE MATERIALS - A. Tokar; L. Matenchuk; S. Myroniuk; M. Shcherbak; V. Khareba (Harčova Nauka ì Tehnologìâ, 2020)
The content of ascorbic acid and phenolic substances in natural juices and unfortified wine materials from garden strawberries of Polka and Pegas varieties was investigated. The content of ascorbic acid was 271-417 mg/dm3 and of phenolic substances – 1280-1500 mg/dm3. The content of these ingredients depends on the variety characteristics (dominant influence) and the weather conditions of the growing season. 230 g of white sugar was added to one dm3 of strawberry juice for the production of unfortified wine materials intended for sweet wines. The wort was pasteurized at 85°C for 5 minutes, cooled and fermented using active dry yeast: the race EC 1118 (France), ENSIS LE-C1, ENSIS LE-1, ENSIS LE-5, ENSIS LE-6 (Spain) in accordance with the manufacturer's recommendations. It has been found that the content of ascorbic acid and phenolic substances decreases during wort preparation and fermentation. The average loss of ascorbic acid during wort preparation is 17.4% and of phenolic substances – from 1.1 to 4.9%. The reduction in the content of these components due to the dilution of sugar during wort preparation is 14-15%. The duration of fermentation of strawberry worts with an initial mass concentration of invert sugars 274 g/ dm3 is 70-77 days. The output of cleared wine material after fermentation depends on the variety characteristics, the year conditions and the yeast race used, and ranges from 86.9 to 92.7%. Loss of ascorbic acid during wort fermentation averages 49.3%, phenolic substances 21.6%. Ascorbic acid content of 86-158 mg/dm3 and phenolic substances of 720–1080 mg/dm3 were found in unfortified strawberry wines. In particular, according to the average data of two years, the content of phenolic substances in the wine materials from strawberries of the Polka variety were 197 mg/dm3 higher than their content in the wine materials from the berries of the Pegas variety.